Physicians\' Knowledge about Different Radiobiology Aspect and Radiation Dose, Received by Patients in Diagnostic Radiology in 2013 - Aram Rostami; Mohamad Reza Cheshmyazdan; Mahdi Payande Vafa; Leila Kia; Fateme Saadat Ghoreishi (Tehran University of Medical Sciences, 2016)
Background and Aim: The first step in reducing patient dose can be administered at the radiological examinations are taken. Since physicians request radiological tests, this study examined physicianschr('39') knowledge of the risks of radiological examinations. Materials and Methods: This descriptive, analytical and cross-sectional study was conducted in 160 general practitioners and specialistschr('39') physicians. Based on the estimated dose posterior-anterior hand X-ray, and put it as a single exposure, medical information of physicians about the patient dose in diagnostic radiology tests were examined. The validity of the questionnaire was confirmed by expert panel, and its reliability was 0.80 by Alpha-Cronbach technique. Results: Most of the general practitioners and specialists did not estimate correctly the radiation dose received by patients in the posterior-anterior hand X-ray, and majority of them underestimated the radiation dose of other radiological examination. The results showed that 48% of General Physician and 5/53% of specialist physicians were familiar with the unit dose. Conclusion: Training of physicians in the field of radiology patients received doses can be an effective measure for reducing doses to patients.